A review of the oxygen vacancy ordering in surrogate structures simulating Pu-based nuclear ceramics - Charlton, Henry; Baldinozzi, Gianguido; Patel, Maulik (Frontiers in Nuclear Engineering, 2023)
Advanced nuclear power systems and nuclear fuel cycles will require nuclear fuels capable of higher burnup and with higher transuranic concentrations than those previously developed for current nuclear power plants. Expensive qualification tests are required to validate the thermal and mechanical performance of fuels in normal and accident-scenario operations. Research of surrogate systems with specific properties and characteristics of advanced nuclear fuels can be an effective way to frame the problem, reduce costs, and support the technical development of future research. From this perspective, lanthanide counterparts like mixed oxides of Ce and Nd can provide replica systems for many technological properties of the actual fuels. These ceramic systems can lead to a better understanding of the fundamental irradiation processes responsible for the evolution of their microstructures, the interplay with charge and defect localisation, and the evolution of their mechanical properties. In non-stoichiometric MO2−x binary systems (M = Ce, Pr, Tb), there is evidence of systematic ordering of vacancies resulting in a deviation from the ideal fluorite structure and the formation of several intermediate fluorite-related phases. Substitution of the 4+ cations with 3+ cations in these systems drives the formation of oxygen vacancies as a charge compensation mechanism. By analogy with MO2−x systems, a variety of similar intermediate phases would also be expected to form in the MO2:Ln2O3 (Ln = La, Nd, Gd. . . etc). However, in order to achieve chemical homogeneity and charge ordering, prolonged annealing just above the charge ordering transition temperature is required, covering a time-scale determined by the chemical diffusion coefficient. Achieving these conditions with powder metallurgy techniques, commonly employed in literature, is practically impossible. This paper reviews the transport properties and structural features found in these surrogate systems which may be helpful in addressing challenges facing advanced nuclear fuels. We present results of a recent diffraction experiment investigating the structure of neodymium doped ceria synthesised using soft chemical methods. The sample shows a deviation from previous literature as the diffraction data is best described by a monoclinic Ln6O11-type structure (SG P21/c), often referred to as “β phase” in PrO2−x.